(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The linearization approach is used in this contribution to acquire the answers to the variable frequency oscillator equation as well as the modified Ivey’s equation. Differential forms (DF) and the generalized Sundman transformation (GST) are two linearization techniques that are considered. It is found that the modified Ivey’s equation cannot be linearized using differential forms, while the equation for a variable frequency oscillator can. However, using GST, the modified Ivey’s equation can be linearized.